Structural adjustment and the private sector in the Caribbean. - Downes, Andrew S. (1992)
Outlines the nature of structural adjustment programmes and discusses the experience of Caribbean countries with such programmes. Examines the role which the private sector can play in a restructed economy and how this role can be discharged.